Pulmonary arterial wall thickness is increased in Behçet's disease patients with major organ ınvolvement: Is it a sign of severity? - KOCAKAYA, DERYA; DİRESKENELİ, RAFİ HANER; ALİBAZ ÖNER, FATMA (My University, 2023)
Objectives Behcet\"s disease (BD) is a unique systemic vasculitis mainly involving veins, in contrast to other vasculitides. Prior studies have shown that pulmonary arteries (PAs) have a similar structure to systemic veins. In this study we aimed to assess PA wall thickness by transthoracic echocardiography (TTE) in BD patients compared with healthy controls (HCs) and patients with non-inflammatory pulmonary embolism (NIPE). Methods Patients with BD (n = 77) and NIPE (n = 33) and HCs (n = 57) were studied. PA wall thickness was measured from the mid-portion of the main PA with TTE by two cardiologists blinded to cases. Results PA wall thickness was significantly lower in HCs [3.6 mm (s.d. 0.3)] compared with NIPE [4.4 mm (s.d. 0.5)] and BD [4.4 mm (s.d. 0.6)] (P < 0.001 for both). PA wall thickness was similar between BD and NIPE (P = 0.6). Among patients with BD, PA wall thickness was significantly higher in patients with major organ involvement compared with mucocutaneous limited disease [4.7 mm (s.d. 0.4) vs 3.7 (0.4), P < 0.001], HCs and NIPE (P < 0.001 and P = 0.006, respectively). PA wall thickness was comparable between patients with vascular and non-vascular major organ involvement [4.6 mm (s.d. 0.5) vs 4.7 (0.3), P = 0.3]. Conclusion We observed that PA wall thickness was significantly higher in BD with major organ involvement compared with patients with only mucocutaneous limited disease, HCs and NIPE. These results suggest that increased PA wall thickness may be a sign of severe disease with major organ involvement in BD.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; İç Hastalıkları; İmmünoloji ve Romatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Chest Diseases and Allergy; Internal Diseases; Immunology and Rheumatology; Klinik Tıp (MED); Klinik Tıp; ROMATOLOJİ; SOLUNUM SİSTEMİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; RHEUMATOLOGY; RESPIRATORY SYSTEM; MEDICINE, GENERAL & INTERNAL; Solunum Bakımı; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Romatoloji; Akciğer ve Solunum Tıbbı; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Respiratory Care; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Rheumatology; Pulmonary and Respiratory Medicine; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Behcet's disease; pulmonary artery wall thickness; echocardiography; ULTRASOUND